2018
DOI: 10.18089/tms.2018.14106
|View full text |Cite
|
Sign up to set email alerts
|

Birdwatcher profile in the Ria Formosa Natural Park

Abstract: In the Algarve the potential for birdwatching tourism is widely recognized, especially in the Ria Formosa Natural Park (RFNP). This study aims to describe birdwatchers' profile in the RFNP. For this purpose, a survey was applied. The results show that the most frequent nationalities of birdwatchers are: British (39%), Dutch (17%) and Portuguese (17%). The majority of birdwatchers are male (55%) and married (57%). The average age is 50 years old. They are highly educated (74% have an academic degree). Concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…This is probably related to the fact that hunting and fishing and associated conservation expenditures tend to be more popular in North America [25]. Only a few studies were outside this area, e.g., in a national park in Thailand [7], in Taiwan [26], Hong Kong [27], Portugal [28], South Africa [29], or Poland [30]. Recently, Hermes et al [31] quantified the nature-based recreation cost in Germany as €151.3 billion, including travel costs, on-site expenses, and opportunity costs, suggesting that birding is an emerging market in Germany.…”
Section: Review Of Literature 21 Recreation Specializationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably related to the fact that hunting and fishing and associated conservation expenditures tend to be more popular in North America [25]. Only a few studies were outside this area, e.g., in a national park in Thailand [7], in Taiwan [26], Hong Kong [27], Portugal [28], South Africa [29], or Poland [30]. Recently, Hermes et al [31] quantified the nature-based recreation cost in Germany as €151.3 billion, including travel costs, on-site expenses, and opportunity costs, suggesting that birding is an emerging market in Germany.…”
Section: Review Of Literature 21 Recreation Specializationmentioning
confidence: 99%
“…This scale refers to self-reported real behavior. Behavior contained the number of birding trips taken last year (at least 2 km away from home; [6,18]), number of days spent for birding last year [6,7,27,28], number of bird species on lifelist [26], number of bird books owned [16], replacement value of the total equipment [7,26,27], and number of species on a national list (this study). Open-ended questions were z-transformed prior to analysis.…”
Section: Behaviormentioning
confidence: 99%
“…The dominance of male respondents compared to female respondents followed Nicolene Conradie (2015) in British and Dutch Birdwatching Fair participation. Different results were found by Frątczak et al (2020); Omar et al (2019); Costa et al (2018), andMaple et al (2010) who found that more female respondents became the birdwatchers. Nevertheless, Eubanks et al (2004) found that there was an insignificant difference between birdwatcher genders, which can be said that birdwatching is a gender-equal activity.…”
Section: Respondent Demographicmentioning
confidence: 75%
“…Globally, there are still minimum studies about the birdwatching demand (Steven, 2015), including Indonesia. A comprehension about birdwatchers will be the basic of birdwatching management, therefore this recreation can continuously develop with the right target following the recreation actor eagerness (Costa et al, 2018;Ma et al, 2018). This study aimed to analyze the birdwatcher characteristics in Indonesia based on the demographical and experience aspects.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior scale refers to self-reported real behavior. This scale contained the number of birding trips taken last year (at least 2 km away from home; McFarlane and Boxall, 1996), number of days spent in birding during the last year (Cheung et al, 2017;Costa et al, 2018;Hvenegaard, 2002), the total number of bird species on the lifelist (Tsaur & Liang, 2008), the number of bird books owned (McFarlane, 1994), replacement value of the total equipment in € (Cheung et al, 2017;Hvenegaard, 2002;Tsaur & Liang, 2008) and the number of species on a national list, concerning Germany, Austria and Switzerland (developed for this study). All these questions were open ended to allow a comparison but were z-transformed prior to analysis.…”
Section: Behaviormentioning
confidence: 99%